Development of molecularly imprinted polymer for the selective recognition of the weakly interacting fenamiphos molecule. (15th August 2022) - Nasraoui, Chaima; Jaoued-Grayaa, Najeh; Vanoye, Laurent; Chevalier, Yves; Hbaieb, Souhaira
Graphical abstract: Highlights: Efficient MIP in spite of weak interactions with fenamiphos insecticide. MIPs as thin film onto modified silica surface for fenamiphos extraction. Adsorption behaviors of fenamiphos show the wide range of possible functional monomers. Quantitative assessment of MIPs adsorption isotherms by the Langmuir–Volmer model. Abstract: The possible manufacture of Molecularly Imprinted Polymers (MIPs) under the conditions of weak interaction between the functional monomer and template molecule is addressed with the help of the case of the Fenamiphos organophosphorus insecticide. The choice of the functional monomer is addressed by investigating MIPs prepared by the surface imprinting technique using three very different types of monomers (methacrylic acid, 4-vinylpyridine and 2–(methacryloyloxyethyl)trimethylammonium chloride), a solid silica support grafted with 3-mercaptopropyltrimethoxysilane on its surface; ethylene glycol dimethacrylate as the cross-linker and acetonitrile as solvent. The prepared materials were characterized by IR, solid state 13 C NMR, TGA, DLS, BET and TEM. Their performance as adsorbents were evaluated by modeling their experimental adsorption isotherms using the Langmuir–Volmer model. All MIPs show similar adsorbent performance although the functional monomers were quite different and the interactions with fenamiphos were weak. The latter were assessed by 1 H and 31 P NMR experiments in DMSO‑ d6 solution. The adsorption process presented weakly exothermic and endothermic behavior onto molecular imprints and non-specific sites respectively. The selectivity for adsorption of fenamiphos with respect to its sulfone and sulfoxide metabolites was quite high.